FORMATION OF STUDENT'S RESEARCH SKILLS: EXPERIENCE OF INDIVIDUAL WORK ORGANIZATION BY BIOSTATISTICS (WITHIN THE TEMPUS IV, PROJECT MUMEENA) - Децик, О. З.; Бурак, О. Л.; Стовбан, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
According to recommendations received by the project MUMEENA, at the Department of Social medicine, organization of health service and medical law of IFNMU, method of forming skills of work with scientometric databases and scientific literature for medical faculty students was developed. It was designed for implementation during study of obligatory discipline Biostatistics on the 4th course by appropriate form of individual work of students. Method contains: algorithm of individual tasks realization, thematic plan of teacher's consultations for monitoring and correcting of each stage of the task and the final evaluation criteria mastering skills (from 0 to 8 points). Scores for the individual tasks were added to the current success of the student. During 2013 year 8 students volunteered to perform such independent work, in 2014 - 13 students, mainly from members of student scientific society. The final survey showed that this form of individual work of students meets the current requirements of evidence-based medicine and allows forming necessary practical skills of work with scientific literature. We offer to introduce similar forms of individual work of students from all subjects studied at the department for students’ quantity enlargement, and increase interdisciplinary integration with clinical and other disciplines of 1-3 courses that allow students to form an informed demand for relevant knowledge.